Fraud Diamond Analysis in Revealing Asset Misappropriation with Fraud Risk Assessment as a Moderating Variable: a Perspective of the Fraud Diamond Theory - Zati Rizka Fadhila; Anis Chariri; Rr Sri Handayani (KEUNIS, 2026)
Asset misappropriation is one of the most frequent and financially destructive types of occupational fraud, particularly in the public sector. Nevertheless, the behavioral and governance mechanisms contributing to this fraud have not received much attention in existing studies. Therefore, this study aims to evaluate the determinants of asset misappropriation by employing the Fraud Diamond Theory, which comprises elements of pressure, opportunity, rationalization, and capability. Furthermore, the analyses also explore the moderating role of Fraud Risk Assessment (FRA) as a detection-oriented governance mechanism, where its positive correlation with misappropriation is hypothesized to indicate increased detection capacity rather than control failure. Data obtained from 312 respondents from public organizations in Indonesia were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that opportunity and capability significantly influence asset misappropriation, while pressure and rationalization show no significant effect. Meanwhile, FRA serves a dual role: 1) it positively affects asset misappropriation through improved detection; and 2) it negatively moderates the relationship between opportunity and asset misappropriation. This reflects the effectiveness of FRA in limiting the exploitation of weak controls. By elucidating FRA’s dual role in governance and detection, this study contributes to the fraud theory and carries practical implications for the enhancement of fraud management through integrated surveillance, audit coordination, and real-time risk analytics.